Gaining extra information from herbicide trials - analysing field trials of the region Hannover from 2003 to 2009 - Fritzsche, Robert (Julius-Kühn-Archiv, 2012)
Crop protection services gather data on pesticides in the context of product registration and for region-specific extension. For this purpose, the region Hannover conducts field trials, which depending on the initiators can be based on different designs. The purpose of this study was to see if it is possible to extract additional data from these data sets by joint analysis. The 1076 data sets are based on 89 trials conducted in 40 locations in a radius of 50 km around the city of Hannover from 2003 to 2009. The region is situated in two ecoregional zones. There were area-specific differences in crop- and herbicide management. About half of the locations were chosen as trial location for herbicides only once and about 70 % of all treatments were tested only in one year. Consequently, possible year-effects remained hidden. Data with regard to the grass weeds, Alopecurus myosuroides (ALOMY) and Apera spica-venti (APESV), were particularly abundant. In 74 % of the trials, the density of ALOMY was > 200 ears per square meter. In contrast, in only 5 % of the trials was the density of APESV > 200 panicles per square meter. However, APESV will lead to higher yield losses than ALOMY at similar ear density. Furthermore, ALOMY predominantly occurred in locations that had the potential to produce higher crop yields than locations with APESV. Analyses of the timing of the surveys showed that crop yield could be best predicted based on weed surveys in early spring (R² = 0.54), whereas correlations with surveys conducted in autumn were weak (R² = 0.25). The results of this study show that the joint analysis of herbicide trials can yield valuable new insights. Joint analysis of herbicide efficiency over all trials could not be conducted due to lack of replication of trials with identical variants over time.